SEMIOTIC ANALYSIS OF DA'WAH CONTENT IN DIGITAL PAINTING ART: A STUDY OF THE INSTAGRAM SOCIAL MEDIA ACCOUNT @_ZUKKK - Muhammad Fauzan Fayrozi; Fakhrur Rozi (Journal Analytica Islamica, 2026)
This study aims to analyze the construction of the meaning of da'wah in digital painting artworks published through the Instagram account @_zukkk using Roland Barthes' semiotic approach. This study is motivated by the transformation of da'wah in the digital era, where religious messages are increasingly conveyed through visual media that align with the communication characteristics of the millennial and Generation Z generations. This study uses a qualitative approach with a semiotic analysis method that maps meaning at three levels, namely denotation, connotation, and myth. The research data is in the form of uploaded digital artworks that display a representation of a Muslim performing a bowing movement under a large tree, with the surrounding natural elements depicted as bowing as well. The results show that at the denotative level, the artwork represents the practice of prayer as a form of ritual obedience. At the connotative level, the visualization builds the meaning of spiritual harmony between humans and nature in submission to Allah. Meanwhile, at the mythical level, this artwork constructs an ideological narrative about the cosmological submission of the entire universe to the Creator. This study concludes that digital painting serves not only as an aesthetic expression but also as an effective and contextual visual da'wah medium in the social media era. These findings contribute to the development of digital da'wah communication studies by emphasizing the role of visual art as an adaptive, reflective, and relevant da'wah strategy within contemporary visual culture.